Effect of medical Qigong on cognitive function, quality of life, and a biomarker of inflammation in cancer patients: a randomized controlled trial - Oh, B.; Butow, P.; Mullan, Barbara; Clarke, S.; Beale, P.; Pavlakis, N.; Lee, M.; Rosenthal, D.; Larkey, L.; Vardy, J. (Springer, 2012)
Purpose. Cancer patients often experience diminished cognitive function (CF) and quality of life (QOL) due to the side effects of treatment and the disease symptoms. This study evaluates the effects of medical Qigong (MQ; combination of gentle exercise and meditation) on CF, QOL, and inflammation in cancer patients. Methods. Eighty-one cancer patients recruited between October 2007 and May 2008 were randomly assigned to two groups: a control group (n = 44) who received the usual health care and an intervention group (n = 37) who participated in a 10-week MQ program. Self-reported CF was measured by the European Organization for Research and Treatment of Cancer (EORTC-CF) and the Functional Assessment of Cancer Therapy—Cognitive (FACT-Cog). The Functional Assessment of Cancer Therapy—General (FACT-G) was used to measure QOL. C-reactive protein (CRP) was assessed as a biomarker of inflammation. Results. The MQ group self-reported significantly improved CF (mean difference (MD) = 7.78, t 51 = −2.532, p = 0.014) in the EORTC-CF and all the FACT-Cog subscales [perceived cognitive impairment (MD = 4.70, t 43 = −2.254, p = 0.029), impact of perceived cognitive impairment on QOL (MD = 1.64, t 45 = −2.377, p = 0.024), and perceived cognitive abilities (MD = 3.61, t 45 = −2.229, p = 0.031)] compared to controls. The MQ group also reported significantly improved QOL (MD = 12.66, t 45 = −5.715, p < 0.001) and had reduced CRP levels (MD = −0.72, t 45 = 2.092, p = 0.042) compared to controls. Conclusions. Results suggest that MQ benefits cancer patients’ self-reported CF, QOL, and inflammation. A larger randomized controlled trial including an objective assessment of CF is planned.